If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 14 = 56 Reorder the terms: 14 + b = 56 Solving 14 + b = 56 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + b = 56 + -14 Combine like terms: 14 + -14 = 0 0 + b = 56 + -14 b = 56 + -14 Combine like terms: 56 + -14 = 42 b = 42 Simplifying b = 42
| 8x+2(1.5x)=400 | | 4r+s=-14 | | (6x-20)= | | -7x+11=60 | | -2x-4=-x+0 | | (t+3)(t+8)=t(t+5)+168 | | 18-2z=6-4 | | -6y=36x-72 | | 2x^3+4x^2+10x=0 | | 7x-2=34+x | | 4y+7y=66 | | 5n+10-8=2x | | 13a+50=360 | | 2(x-7)+3(x-1)=4+3 | | 4x+4y=-32 | | X+18=-4 | | 2y^2-7=25 | | x-4/8=15 | | -3(8x+2)+4(5x-1)= | | (3x^2y-xy)dx+(2x^3y^2+x^3y^4)dy=0 | | 3/5x-4=2 | | x-14=66 | | -5x-6=x-48 | | 4(-5x+8)-(x+5)=-15 | | 9xm+19=55 | | 4(-3x-6)= | | m(m-7)= | | 2*x-7=1 | | -2w-3(4z-5w)-32= | | 4c-3d=-20 | | 2x^2+4x-31=0 | | 3+ln(27x)=18-2ln(x) |